Study on food safety issues in Kedah, Malaysia: A Case on Food Service Operators - Fatin Aiman, Abd Latiff (2020)
Food poisoning has a significant impact towards the economic, environmental and social aspects. The complexity of global food poisoning cases has made the government and related food agencies established a new regulation as an improvement and to complement the previous food safety regulations. This research explored and explained the pattern and drivers of food poisoning cases in Malaysia. The present study demonstrated knowledge, attitude and practices (KAP) model as a theoretical research framework with the purpose to determine the true causes of food poisoning incidents occurred in 2013 that resulted in deaths which accessed on the KAP pertaining to food safety among food service operators, and thus concludes the level of food safety compliance in Kedah. In regards of the research instruments, the present study employed both qualitative and quantitative research designs, and it was conducted in two phases. In the first phase of data collection method, two experts from Food Safety and Quality Division, Ministry of Health Malaysia were selected as respondents for semi-structured interviews. Meanwhile, self-administered questionnaire surveys were deployed as the second instrument in the present study. A total of 360 questionnaire sets were distributed among food service operators in Kedah district including Kulim, Sungai Petani, Gurun, Yan, Alor Setar, Jitra, Kubang Pasu and Changlun. Both qualitative and quantitative techniques were used as systematic tools to test and validate the model. Findings of the present study demonstrated that the attitude of food service operators during food preparation processes were synonymous with the occurrence of food poisoning incidence in Kedah. Whereas food service operators’ knowledge and handling practices has a significant relationship toward food handling practices and food safety standard compliance. The present study also highlights on the implications and limitations of the study as well as the suggestions for future research.